A assistência e a exposição de crianças na formação de um território (Rio Grande de São Pedro, Séculos XVIII e XIX) - Silva, Jonathan Fachini da (Universidade do Vale do Rio dos Sinos, 2019)
This study approaches the phenomenon of both exposure and assistance to the children at the southern part of the Portuguese America, focusing in parishes with municipal councils, in the second half of eighteenth century until the first decades of the nineteenth century. Based on all the experience and knowledge accumulated for the study of the administration of the exposition phenomenon in Porto Alegre, now the perspective is directed to the other localities, expanding the analysis spectrum during the formation and consolidation of Rio Grande do Sul de São Pedro. It is a frontier area, with a diverse population and a large territorial extension. The main goal is to understand a social practice such as this brought by European settlers through the Atlantic has spread in this territory, as well as indigenous and African populations interacted with it, either exposing children or taking part assisting the rejected ones. In this sense, we understand the role of the African ancestry people and indigenous population settled to the administration and maintenance of this practice. In order to achieve the proposed goals, we intend to use a set of ecclesiastical and notary sources, explored through the intersection of the information contained, especially in the Parish Registers, as well as sources referring to the administration of assistance to the exposed children produced by Southern Chambers. The main theoretical and methodological references taken for this study are those of Historical Demography, which offers us adequate methods of analysis, the variation of scale that allows us to perceive the rationalities in the actions of the historical subjects based on the specificities of our context, as well as a historiographical base on this theme in Social History, Poverty and Assistance History.
Keywords: Expostos; Assistência; Câmara; Rio Grande de São Pedro; Exposed; Assistance; City Councill; Rio Grande de São Pedro; ACCNPQ::Ciências Humanas::História